Entomopathogenic Nematodes and Their Symbiotic Bacteria from the National Parks of Thailand and Larvicidal Property of Symbiotic Bacteria against Aedes aegypti and Culex quinquefasciatus - Aunchalee Thanwisai; Paramaporn Muangpat; Wipanee Meesil; Pichamon Janthu; Abdulhakam Dumidae; Chanakan Subkrasae; Jiranun Ardpairin; Sarunporn Tandhavanant; Timothy P. Yoshino; Apichat Vitta (Biology, 2022)
Entomopathogenic nematodes (EPNs) are insect parasitic nematodes of the genera Het-erorhabditis and Steinernema. These nematodes are symbiotically associated with the bacteria, Photorhabdus and Xenorhabdus, respectively. National parks in Thailand are a potentially rich resource for recovering native EPNs and their symbiotic bacteria. The objectives of this study are to isolate and identify EPNs and their bacterial flora from soil samples in four national parks in Thailand and to evaluate their efficacy for controlling mosquito larvae. Using a baiting method with a Galleria mellonella moth larvae and a White trap technique, 80 out of 840 soil samples (9.5%) from 168 field sites were positive for EPNs. Sequencing of an internal transcribed spacer resulted in the molecular identification of Heterorhabditis nematode isolates as H. indica, H. baujardi and Heterorhabditis SGmg3, while using 28S rDNA sequencing, Steinernema nematode species were identified as S. guang-dongense, S. surkhetense, S. minutum, S. longicaudum and one closely related to S. yirgalemense. For the symbiotic bacterial isolates, based on recA sequencing, the Photorhabdus spp. were identified as P. luminescens subsp. akhurstii, P. luminescens subsp. hainanensis and P. luminescens subsp. australis. Xenorhabdus isolates were identified as X. stockiae, X. indica, X. griffiniae, X. japonica and X. hominickii. Results of bioassays demonstrate that Photorhabdus isolates were effective on both Aedes aegypti and Culex quinquefasciatus. Therefore, we conclude that soil from Thailand’s national parks contain a high diversity of entomopathogenic nematodes and their symbiotic bacteria. Photorhabdus bacteria are larvicidal against culicine mosquitoes and may serve as effective biocontrol agents.